1996
DOI: 10.1200/jco.1996.14.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Management of residual mass in advanced seminoma: results and recommendations from the Memorial Sloan-Kettering Cancer Center.

Abstract: Patients with advanced seminoma who have normal radiographs or residual masses less than 3 cm after chemotherapy can be observed without further intervention. The following three options exist for patients with a residual mass > or = 3 cm: observation, radiotherapy, or surgical intervention. We prefer the latter to define response, resect viable tumor when possible, and direct further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(70 citation statements)
references
References 19 publications
1
58
0
11
Order By: Relevance
“…Attempted surgical removal can be difficult. In most cases, the masses will resolve in time, but if larger than 3 cm the chance of active malignancy is higher (Puc et al, 1996). If PET scanning is available, then data from De Santis et al (2004) suggests that 80% of patients with active disease can be identified and should be undertaken for masses 43 cm.…”
Section: Stages Iic -Ivmentioning
confidence: 99%
“…Attempted surgical removal can be difficult. In most cases, the masses will resolve in time, but if larger than 3 cm the chance of active malignancy is higher (Puc et al, 1996). If PET scanning is available, then data from De Santis et al (2004) suggests that 80% of patients with active disease can be identified and should be undertaken for masses 43 cm.…”
Section: Stages Iic -Ivmentioning
confidence: 99%
“…The positive predictive value and negative predictive value of FDG PET, irrespective of tumor size, were 100% and 96%, respectively.The two false negatives were seen in tumors #3 cm in size. Size .3 cm or #3 cm was confirmed to be a predictor of residual disease, as it has been in other series, with a cancer rate of 37% and 8%, respectively [7][8][9][10]. This series was followed up 1 year later and reported an additional false negative (3 of 11) in tumors ,3 cm but maintained its perfect positive predictive value for a final sensitivity and specificity of 80% and 100%, respectively [11].…”
Section: Imaging After Chemotherapymentioning
confidence: 59%
“…There is little evidence for routine adjuvant treatment after combination chemotherapy (Schultz et al, 1989;Duchesne et al, 1997). It has been suggested that residual masses more than 3 cm in diameter early in the period following chemotherapy may be at greater risk of containing viable seminoma (Motzer et al, 1988;Puc et al, 1996) and the protocol therefore recommended a biopsy of any residual mass more than 5 cm in diameter. In this trial, only 5 residual masses in 4 patients in this time period were resected (1) or biopsied (3) and one revealed viable seminoma.…”
Section: Discussionmentioning
confidence: 99%